M.AI.A: an AI-powered ESL writing platform with reflective prompts / Iza Faradiba Mohammad Patel ... [et al.] - Mohammad Patel, Iza Faradiba; Nasrudin, Nur Hasni; Ahmad Junid, Rosida; Awaludin, Farahidatul Akmar; Wan Mohd Rashidi, Wan Faridatul Akma (2023)
In English as a Second Language (ESL) education, fostering reflective thinking and effective writing skills has long been a challenge. This innovation introduces a solution - a dynamic I-powered ESL writing platform aimed to cultivate reflective learning practices and improve writing proficiency. The platform integrates cutting-edge natural language processing (NLP) techniques to offer real-time grammar and vocabulary feedback while strategically introducing reflective prompts aimed at prompting critical analysis of writing choices. By combining automated error identification with opportunities for self-assessment, the platform engages students in active reflection, enhancing their awareness of language accuracy and essay principles. The proposed platform leverages a carefully curated dataset to train a specialized AI model capable of identifying errors and generating targeted suggestions for ESL writing. Additionally, the system generates contextually relevant reflective prompts that challenge students to explain their word choices, sentence structures, and overall narrative strategies. These prompts encourage learners to deepen their metacognitive understanding of their writing, thereby fostering a holistic improvement in language proficiency and reflective thinking. To enable an adaptive and personalized learning experience, the platform adapts the frequency and complexity of reflective prompts based on each student's progress. This innovation addresses the practical challenges of ESL writing improvement and aligns with the broader pedagogical goals of cultivating critical thinking and self-directed learning. By merging AI technology with reflective learning strategies, the proposed platform stands to revolutionize the ESL education landscape, empowering students to become more proficient and thoughtful communicators in English.